Environmental resource use by agricultural and horticultural commodities - Defra project report IS0205 - Williams, Adrian; Audsley, Eric; Sandars, Daniel (Cranfield University, 2019)
Underlying models used in the report: "Determining the environmental burdens and resource use in the production of agricultural and horticultural commodities." Defra project report IS0205 by the Natural Resource Management Institute, Cranfield University, August 2006. The final report and executive summary are available from the defra site at the link provided.
Keywords: emissions'; 'LCA model'; 'Sustainable Agricultural Development'; 'Horticultural Production not elsewhere classified'; 'Agriculture; Land and Farm Management not elsewhere classified'